Comparison of Student Learning by Using The Strategy Hypnoteaching CTL REACT and Material on Relations and Function in Class VIII MTsN Mulawarman Banjarmasin - Pramita, Lestari (Jurnal PTK dan Pendidikan, 2016)
This study was conducted to examine the differences in student learning outcomes using hypnoteaching the REACT strategy and CTL on material relations and functions. This research is a form of field research (Field Research) with the experimental method. The study population was a class VIII student MTsN Mulawarman Banjarmasin academic year 2015/2016 the number of students as many as 206 students. Samples peneitian is class VIII VIII C and E. Based on the results of the study there was no significant difference mathematics learning outcomes of students who are taught using methods hypnoteaching the REACT strategy and using hypnoteaching in CTL strategy.